The human factor in Argentine agriculture - Marcos Gallacher (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
The objective of this paper is to identify determinants of the reductions in the use of labor observed in Argentine agriculture. The paper focuses on the 2002-2018 period, using data from the last two publications of the Censo Nacional Agropecuario (the census undertaken in 2008 is incomplete). The paper summarizes trends of labor use and firm size in Argentina, and presents three possible hypothesis accounting for observed changes: (a) capital-labor substitution, (b) labor-saving technical change (reduced and no-tillage) and (c) changes in farm size and the types of capital (machines) used.
Keywords: Q1; D2; 330; Agrarberufe; Landwirtschaftlicher Familienbetrieb; Betriebsgröße; Substitutionseffekt; Technischer Fortschritt; Landmaschine; Argentinien